Implementation of Internal Marketing Mix Increasing Sales According to Islamic Economics (Case Study of Kita Merlung Family Building Store) - Zahrah, Zahrah; Rosmanidar, Elyanti; Ferdiansyah, Wahyu; Yuniar, Vita; Ramli, Fauzan; Fitri, Sasmita; Fahrurrozi, Fahrurrozi (International Journal of Economics (IJEC), 2024)
Marketing mix (marketing mix) is used to achieve marketing objectives. Using a qualitative research method, a descriptive approach. The findings show that the implementation of the marketing mix increases the sales volume at the Kita Family Building Store, namely in terms of products it still focuses on building equipment such as cement, sand, bricks, etc. Marketing it using media is very simple and according to the Islamic Economics Perspective, the implementation of the marketing mix for Our Family Building Store is in accordance with Islamic marketing. To a large extent, the concept of Islamic marketing is in accordance, namely in terms of products, always being honest and prioritizing product quality. In terms of price, set the price according to the quality of the product. then in terms of promotion, always emphasize ethics in business, don't cheat, don't sell products that are forbidden by religion, never force consumers to buy their products, don't badmouth other people's businesses in marketing their products and from distribution places/channels, namely providing a sense of comfort and easy access for consumers.